1999
DOI: 10.1590/s0001-37141999000100007
|View full text |Cite
|
Sign up to set email alerts
|

Enzootic bovine Leukosis: development of an indirect enzyme linked immunosorbent assay (I-Elisa) in seroepidemiological studies

Abstract: Bovine Leukemia Virus (BLV) is the etiologic agent of Enzootic Bovine Leukosis, a retrovirus exogenous to the bovine species. Once infected, there is no detectable viraemia but instead there is a strong and persistent immunological response to BLV structural proteins, essentially the gp51 envelope glycoprotein and the mayor core protein p24. We describe the test procedure of an indirect ELISA (I-ELISA) using polyclonal reagents for the detection of antibodies to BLV. For comparison, the sera were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
4
0
4
Order By: Relevance
“…This provided a high specificity and reduced the risk of false positive results. This cutoff value is in accord with Gonzalez who reported that mean value + 2SD (0.11) and mean + plus 3SD (0.18) represent good specificity and sensitivity of the test, respectively (Ridge and Vizard 1993;Gonzalez et al 1999).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This provided a high specificity and reduced the risk of false positive results. This cutoff value is in accord with Gonzalez who reported that mean value + 2SD (0.11) and mean + plus 3SD (0.18) represent good specificity and sensitivity of the test, respectively (Ridge and Vizard 1993;Gonzalez et al 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Using a crude antigen in an indirect ELISA can cause a high background (Gonzalez et al 1999); in this regard, we set up a cutoff value on the basis of the high numbers of negative sera (confirmed by CI-ELISA) from different herds and various ages. To establish a reliable cutoff that covers 99% of negative control set of sera, threefold standard deviation (SD) value above the mean of negative control absorbances was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Impurities are responsible for high background values and for non specific reactions. Usually, high purification of antigens increases productions costs (González et al, 1999a). The polymerase chain reaction (PCR) is a useful and sensitive tool for fast and early detection of BLV proviral DNA in blood, organs and tumoral samples (González et al, 1999b).…”
Section: Dementioning
confidence: 99%
“…Given the multiple transmission routes, both natural and iatrogenic and the minimum volumes of peripheral blood required to transmit the virus, this disease has a high potential for disease transmission [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…In experimentally infected animals anti-gp51 antibodies seem to be the first to appear with titres consistently higher than anti-p24 antibodies [7] [8] [9]. Other authors reports that high sensitivity tests are able to detect anti-p24 antibodies before the appearance of anti-gp51 antibodies; and the anti-p24 antibodies could be an equal or greater degree than anti-gp51 [3] [10]. The immunoglobulin isotype in the immune response varies according to the stages of LEB disease, in asymptomatic animals IgM and IgG1 anti p24 and gp51were detected, whereas the detection of IgA occurs in animals with lymphoma [11].…”
Section: Introductionmentioning
confidence: 99%